The Place Of Court Dance And Music In The Javanese Kratons And Its Relation To The Political Situation - R. M. Soedarsono (Humaniora, 2002)
On February 13, 1755, the kingdom of Mataram of Central Java was formally divided into two – the Kasunanan of Surakarta under Sunan Paku Buwana III (1749-1788) and the Kasultanan of Yogyakarta under Sultan Hamengku Buwana I (also known as Sultan Mangkubumi, 1749-1792). Under the Giyanti Contract, which was supervised by the Dutch, Paku Buwana III gained the eastern part of the realm, while Hamengku Buwana I the western part, including one-half of the 20,000 reals paid annually by the Dutch for the lease of the coastal regions. Hamengku Buwana also received one-half of the royal regalia, including the gamelan. M.C. Ricklefs remarks that two days after the conclusion of the contract, Sultan Hamengku Buwana I, accompanied by Hartingh, and their entourages proceeded to Jatisari, midway between Giyanti and Surakarta. The Babad Mangkubumi reads that Sunan Paku Buwana III arrived shortly thereafter to the sound of Mangkubumi’s gamelan. On this occasion Paku Buwana III presented the Sultan with a kris, Kyai Kopek, handed down from the wali Sunan Kalijaga. The Javanese court gamelan which were considered part of the royal regalia were possibly the gamelan Kodhok Ngorek, gamelan Monggang, and the gamelan Sekati. Along with the other regalia such as sacred weapons, those three gamelan also gained honorific name Kangjeng Kyai. They were only played in some specific events, such as the event of honoring the official arrival of Paku Buwana III at Jatisari to meet his uncle Hamengku Buwana I. This official reception which signified the peaceful relationship between Paku Buwana III and Hamengku Buwana I was celebrated by the sound of Hamengku Buwana’s gamelan, Kangjeng Kyai Monggang.